2022
DOI: 10.1021/jacsau.2c00120
|View full text |Cite
|
Sign up to set email alerts
|

Network Formation and Physical Properties of Epoxy Resins for Future Practical Applications

Abstract: Epoxy resins are used in various fields in a wide range of applications such as coatings, adhesives, modeling compounds, impregnation materials, high-performance composites, insulating materials, and encapsulating and packaging materials for electronic devices. To achieve the desired properties, it is necessary to obtain a better understanding of how the network formation and physical state change involved in the curing reaction affect the resultant network architecture and physical properties. However, this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 300 publications
1
55
0
Order By: Relevance
“…Epoxy resins, an important class of thermosetting polymers, are widely used as adhesives and composite materials in a variety of manufacturing industries ranging from aerospace and automotive engineering to microelectronics, thanks to their excellent mechanical strength, thermal stability, and chemical resistance. Epoxy resins, generally obtained via the curing reaction of epoxy and hardener compounds, are amorphous and highly cross-linked networks with a glass transition temperature ( T g ) well above room temperature. , Thus, under ambient conditions, they are relatively brittle materials with a poor resistance to crack initiation and propagation . Over the past few decades, many attempts have been devoted to improving the fracture performance of epoxy materials by adding a second micro/nanophase of dispersed fillers into reaction mixtures prior to the network formation. Various types of fillers ranging from soft rubbers to hard inorganic particles have been proven to substantially increase the fracture toughness of epoxy resins, although their effects on other thermomechanical properties can vary. A comprehensive comparison of the effect of different filler types on the toughness and thermomechanical properties of epoxy resins has been reported by Kinloch and co-workers. For example, they found that the addition of approximately 10% by mass of silica nanoparticles to an epoxy matrix can simultaneously increase the fracture energy by ∼250% and elastic modulus by ∼15%, while the sample T g remains almost unchanged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epoxy resins, an important class of thermosetting polymers, are widely used as adhesives and composite materials in a variety of manufacturing industries ranging from aerospace and automotive engineering to microelectronics, thanks to their excellent mechanical strength, thermal stability, and chemical resistance. Epoxy resins, generally obtained via the curing reaction of epoxy and hardener compounds, are amorphous and highly cross-linked networks with a glass transition temperature ( T g ) well above room temperature. , Thus, under ambient conditions, they are relatively brittle materials with a poor resistance to crack initiation and propagation . Over the past few decades, many attempts have been devoted to improving the fracture performance of epoxy materials by adding a second micro/nanophase of dispersed fillers into reaction mixtures prior to the network formation. Various types of fillers ranging from soft rubbers to hard inorganic particles have been proven to substantially increase the fracture toughness of epoxy resins, although their effects on other thermomechanical properties can vary. A comprehensive comparison of the effect of different filler types on the toughness and thermomechanical properties of epoxy resins has been reported by Kinloch and co-workers. For example, they found that the addition of approximately 10% by mass of silica nanoparticles to an epoxy matrix can simultaneously increase the fracture energy by ∼250% and elastic modulus by ∼15%, while the sample T g remains almost unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…1−4 Epoxy resins, generally obtained via the curing reaction of epoxy and hardener compounds, are amorphous and highly cross-linked networks with a glass transition temperature (T g ) well above room temperature. 5,6 Thus, under ambient conditions, they are relatively brittle materials with a poor resistance to crack initiation and propagation. 7 Over the past few decades, many attempts have been devoted to improving the fracture performance of epoxy materials by adding a second micro/nanophase of dispersed fillers into reaction mixtures prior to the network formation.…”
Section: Introductionmentioning
confidence: 99%
“…6 The adhesion mechanism of epoxy resins has been extensively studied both theoretically and experimentally. 7–33 At the adhesive interface, the ether group, hydroxy group, and benzene ring of DGEBA play important roles, and their interaction with the adherend surface generates adhesive strength. The structure of the adherend surface also has a significant influence on the interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resins are a typical thermosetting product with excellent physical properties and thus are used in a wide variety of applications as structural and functional materials in transportation equipment and electronic devices. , Although many studies have been conducted to achieve further toughening, , higher adhesive strength, and so forth, the adhesion mechanism to an adherend, especially at the molecular scale, is not yet fully understood. To improve the adhesive strength and durability of epoxy resins, it is important to understand the molecular picture at the interface with an adherend. Generally, the progress of the curing reaction at the interface differs from that in the bulk, and the reaction is suppressed near the interface due to the decreased mobility of the molecules and depletion of the reaction partner . Also, even if the epoxy base and curing agent are stoichiometrically mixed, either component is often segregated at the interface due to the thermodynamic demand, so the interfacial reaction can proceed under a condition, where the stoichiometric ratio is shifted from the originally fed value.…”
Section: Introductionmentioning
confidence: 99%